Back to life. Season 1 [videorecording (DVD)] - Haggard, Daisy, 1978- (Showtime, 2023)
In Miri Matteson's first few weeks out after an eighteen-year stint behind bars for murder, the mystery of her past looms large in her insular small hometown. Life post-prison is not going to be easy. Her attempts to kickstart a new life fall flat, and while her parents try to be supportive, they are having troubles of their own. Will Miri find redemption, or is she doomed to be a middle-aged screw-up?